Mass-coupled relativistic spontaneous collapse models. (24th June 2021) - Jones, C; Gasbarri, G; Bassi, A
Abstract: Currently there is not a satisfactory relativistic spontaneous collapse model. Here we show the impossibility of a simple generalization of the continuous spontaneous collapse (CSL) model to the relativistic framework. We consider a mass coupled model as in the non-relativistic limit this gives the CSL model. We show that a Lorentz covariant collapse equation cannot simultaneously satisfy the following conditions: (i) to avoid a divergent rate of energy, (ii) to prevent superluminal signalling.